Pros and Cons of Portal Vein Embolization With Hematopoietic Stem Cells Application in Colorectal Liver Metastases Surgery - Treska, Vladislav; Bruha, Jan; Liska, Vaclav; Fichtl, Jakub; Prochazkova, Kristyna; Petrakova, Tereza; Hosek, Petr (In vivo (Athens, Greece), 2020)
BACKGROUND/AIM: Portal vein embolization (PVE) with autologous stem cells application (aHSC) is a method for future liver remnant volume (FLRV) increase. The aim of the study was to evaluate the positivite and negativite aspects of the method in clinical practice. PATIENTS AND METHODS: PVE with aHSC application was used in 32 patients with colorectal liver metastases and insufficient FLRV. Preoperative number of colorectal liver metastases (CLMs) was 5.2±3.6, CLMs volume 70.1±102.3 mm3 Results: FLRV growth occurred after 2-3 weeks in 31 (96.9%) patients, with volume increase from 528.2±170.5 to 715.4±143.3 ml (p=0.0001). Postoperative thirty days mortality, morbidity was 0% and 3.1%, respectively. Insufficient FLRV growth occurred in one patient. R0 liver resection was performed in 27(87.1%) patients. CLMs volume progression was in 5 (15.6%) patients from 680.0±59.4 to 723.1±57.1 ml (p=0.01). One and two-year overall survival were 88% and 62.9% respectively. Six and twelve-month recurrence-free survival rates were 50.7% and 39.6% respectively. CONCLUSION: PVE with aHSC application is a safe and useful method for FLRV growth. It significantly increases secondary CLMs resectability. However, it can cause CLMs progression. Liver resection should, therefore, be performed as soon as possible after achieving optimal increase of FLRV.
Keywords: nádory jater; Colorectal liver metastases; Humans; terapeutická embolizace; vena portae; Hepatectomy; Portal Vein; hematopoetické kmenové buňky; lidé; Liver Neoplasms; hepatektomie; portal vein embolization; stem cells; kolorektální nádory; future liver remnant volume; předoperační péče; Hematopoietic Stem Cells; Preoperative Care; tumour stimulation; Colorectal Neoplasms; Embolization, Therapeutic